Sustainable Leadership and Performance : Exploring the Mediating Role of Organization Culture - Sagar, Neha; Haque, Syed Nadimul (Prabandhan: Indian Journal of Management, 2025)
Purpose : Sustainable leaders create long-term value for their people by utilizing organizational resources to address environmental and social concerns. This study looked at how organizational culture played a mediating role in the relationship between sustainable leadership (SL) and sustainable performance (SP), assessing performance using variables related to economy, environment, and society. Design/Methodology/Approach : A standardized questionnaire was administered, resulting in 240 valid replies. The measuring model’s reliability and validity were confirmed by Cronbach’s alpha, average variance extracted (AVE), and composite reliability. Structural equation modeling and route analysis were used to investigate both direct and indirect interactions between components. All hypotheses were found to have statistically significant findings (p < 0.05). Findings : The findings showed a strong positive link between SL and SP. Organizational culture was discovered to have a direct positive impact on SP while also mediating the relationship between SL and SP. The research is based on the natural resource-based view (NRBV), dynamic capability theory, and sustainable development theory. Practical Implications : This study provided firms with actionable insights for improving employee performance and long-term sustainability. It highlighted the necessity of creating SL and a strong organizational culture to improve economic, environmental, and social performance. Originality/Value : The study made a novel contribution by combining SL and organizational culture to investigate their cumulative effect on employees’ long-term performance. It emphasized the importance of stakeholder participation, long-term strategic commitment, and alignment with sustainable development goals in creating high-performing, sustainability-driven enterprises.